1979
DOI: 10.1161/01.hyp.1.2.78
|View full text |Cite
|
Sign up to set email alerts
|

Increased resistance and impaired maximal vasodilation in normotensive vascular beds of rats with coarctation hypertension.

Abstract: SUMMARY To study the resistance of normotensive vascular beds in coarctation hypertension, we measured perfusion pressures of pump-perfused (blood), innervated, isolated hindlimbs of 12 rats (Group A) with 4 weeks of hypertension due to partial constriction of the abdominal aorta above the renal arteries, and of three control groups: 11 normotensive rats (Group B) with aorta sham-constricted, nine normotensive rats (Group C) with slight (5%) hindquarters atrophy due to partial constriction of the abdominal aor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Although the differences in placement of the coarctation may cause different physiological effects, the overall clinical differences are small when the coarctation is either thoracic or abdominal and is located proximal to the renal arteries. Bell and Overbeck 21 did hindlimb perfusion studies in the rat and observed increased vascular resistance in these beds. However, the rats were anesthetized during the study, and no direct flow measurements were made.…”
Section: Discussionmentioning
confidence: 99%
“…Although the differences in placement of the coarctation may cause different physiological effects, the overall clinical differences are small when the coarctation is either thoracic or abdominal and is located proximal to the renal arteries. Bell and Overbeck 21 did hindlimb perfusion studies in the rat and observed increased vascular resistance in these beds. However, the rats were anesthetized during the study, and no direct flow measurements were made.…”
Section: Discussionmentioning
confidence: 99%
“…Then, after administration of supplemental anesthesia (chloralose 37.5 or 50 mg/kg and pentobarbital 2.2-3mg/kg i.v. ), we used previously described techniques 2 to measure perfusion pressure in the vascularly isolated, innervated, pumpperfused hindlimb vascular bed. Respiration was natural.…”
Section: Methodsmentioning
confidence: 99%
“…To determine if the effects of nitroprusside are specific to the kidney, an entirely different vascular preparation (isolated strips from tail arteries) was also used. Antonaccio, et al 3 Triner, et al/ Hutchins, et al 6 Bell, et al 8 Godfraind and Dieu 7 Shibata and Cheng 1 Deragon, et al 8 Fink and Brody 9 Castro-Tavares 10 Folkow, et al 13 Specter, et al 11 Deragon, et al 8 Hutchins, et al 8 Hollenberg, et al 12 Cohen, et al 14 -" Control rats received implantations of Silastic strips without DOCA. The implantations were made in the left flank while the rats were under ether anesthesia.…”
mentioning
confidence: 99%